1992
DOI: 10.1677/joe.0.1340205
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic factor in the serum of diabetic rats and its increase during pregnancy

Abstract: Diabetic pregnancy is associated with a high incidence of fetal growth abnormalities which cannot be solely ascribed to fetal hyperglycaemia and hyperinsulinaemia. We therefore examined the possibility of other contributing factors using rats made diabetic with streptozotocin as the experimental model. Blood serum from virgin diabetic rats and, to a much greater extent, from pregnant diabetic rats inhibited [3H]thymidine incorporation by fetal lung cells in culture in a concentration- and time-dependent manner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

1993
1993
1999
1999

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
(48 reference statements)
0
2
1
Order By: Relevance
“…Fractions causing a decrease in [3H]thymidine were selected for further purification. Unlike the factor previously isolated by us from diabetic rat serum (Conliffe et al 1992), these fractions from fetal lungs did not cause cell death. Cytostatic activity was therefore defined as an inhibition of thymidine uptake without causing cell death.…”
Section: Methodscontrasting
confidence: 49%
See 2 more Smart Citations
“…Fractions causing a decrease in [3H]thymidine were selected for further purification. Unlike the factor previously isolated by us from diabetic rat serum (Conliffe et al 1992), these fractions from fetal lungs did not cause cell death. Cytostatic activity was therefore defined as an inhibition of thymidine uptake without causing cell death.…”
Section: Methodscontrasting
confidence: 49%
“…We (Conliffe et al 1992) and others (Liu et al 1992) have shown that thymidine uptake by fetal lung cells in culture correlates with cell number and DNA synthesis. Although fetal lung cytostatic protein bears consider¬ able homology with histone H2B, its amino acid composition suggests that it may be different from rat histone H2B.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation